Impact of multidisciplinary chronic disease collaboration management on self-management of hypertension patients: A cohort study. Issue 28 (15th July 2022) - Huang, Jinding; Xu, Yulan; Cao, Guilan; He, Qin; Yu, Puliang
Abstract : To explore the effect of the interdisciplinary chronic disease management (CDM) model on patients with hypertension. In this intervention study, the subjects were divided into CDM and control groups. Blood pressure control was monitored in both groups. After 1 year of follow-up, the endpoint events of patients and their knowledge, confidence, and behavior in response to the disease were assessed. When compared with the control group, patients in the CDM group obtained higher scores for self-perception and management assessment, and their blood pressure control was also better after discharge. The quality of life and the satisfaction level of patients in the control group were lower than those in the CDM group, while the unplanned readmission rate, incidence of complications, and the average length of hospital stay in the control group were higher than those in the CDM group. CDM model was beneficial to blood pressure control in hypertensive patients. It had also improved the quality of life and the satisfaction level of the hypertensive patients. Our study highlights the importance of the CDM model in the prognosis of hypertensive patients.